VARIATIONS IN FOOD CONTENT OF CROPS AS INFLUENCED BY BIO STIMULANTS IN AN OIL CONTAMINATED SOIL - Offor, U.S; Akonye, L.A; Asouzu, I. A (European Scientific Journal, ESJ, 2015)
A study was carried out at the University of Port Harcourt botanical garden, to determine the influence of bio stimulants on food content of crops grown at two levels of crude oil contamination. Results showed that bio stimulants (sawdust and chromolaena leaves) enhanced protein and carbohydrate accumulation in the crops. However, chromoleana leaves was more effective than sawdust while the test crops-Z. mays and Vigna unguiculata differed in their accumulation potentials in protein and carbohydrate.